Implementasi Peretasan Dan Pengamanan Ssid Pada Jaringan Mikrotik RB941-2ND Dengan Metode Deauther dan Evil Twin - Ziska Andris; Jaka Sutresna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The internet and websites have become a very important need for individuals, organizations, companies and government agencies. Because of the world's great need for the internet and websites, as well as the influence it has on all groups, understanding the benefits of the internet and websites is very important. Information technology security is very important nowadays. This is intended to ensure the security of all information sent or stored via the internet and cannot be accessed carelessly by irresponsible parties. The internet is accessed by many people, including hackers and crackers. For certain reasons, they carry out intrusions that can harm server and computer network owners. The sophistication of attacks and tools on computer networks is inversely proportional to knowledge about intrusions on computer networks. The researcher tries to make useful research, this hack uses the deauther and evil twin method in hacking WiFi networks. The design of this research is microcontroller based, the tool used by the author is NodeMCU for the hacking target using the MikroTik RB941-2ND, then implementing the Hacking and Network Security Simulation of the Mikrotik Rb941-2nd Using the Deauther and Evil Twin Method. The results of this research show that both are techniques that can be used to threaten the security of wireless networks. Preventing Evil Twin attacks involves being aware of the networks you connect to and avoiding unknown wireless networks. Meanwhile, preventing Deauther attacks may involve using additional security tools or protections that can detect and respond to such attacks to maintain the connectivity of your devices. Based on the results of the research that has been carried out, the conclusion that can be concluded is that the researcher was able to hack and carry out security on the internet network in the RT 001 environment with or without a strong password, implemented the assembly of microcontroller tools which are currently easily available on the market, and was able to prevent hacking. RT.001 network with a MikroTik RB941-2ND router and research efforts regarding the use of human error in hacking wireless networks while educating the public about cyber security and how to respond to hacker intrusions.